2022
DOI: 10.1111/jsr.13655
|View full text |Cite
|
Sign up to set email alerts
|

Strange themes in pandemic dreams: Insomnia was associated with more negative, anxious and death‐related dreams during the COVID‐19 pandemic

Abstract: Summary Dreaming and insomnia are important markers of distress in times of crisis. Here, we present a longitudinal, mixed‐methods study examining changes in dreaming between individuals with and without insomnia symptoms and their relationship to mental health during the COVID‐19 pandemic. A global survey examining insomnia symptoms, dreams and mental health was launched in April 2020 and followed participants over 12 months. Of 2240 participants, 1009 (45%) reported dream changes at baseline. A hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Furthermore, our results are only partly consistent with recent longitudinal studies on dreaming during the time of COVID-19 (e.g., Alfonsi et al, 2022;Conte et al, 2022;Gorgoni, Scarpelli, Alfonsi, Annarumma, et al, 2022;Meaklim et al, 2023;Scarpelli et al, 2021Scarpelli et al, , 2022. Indeed, during the first wave of the COVID-19 pandemic, participants reported higher negative emotions and longer MRDs; during the second wave, participants reported higher positive emotions and lower presence of sensory impressions in their MRDs, as well as more realistic and shorter MRDs; while, during the third wave, participants reported lower positive emotions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, our results are only partly consistent with recent longitudinal studies on dreaming during the time of COVID-19 (e.g., Alfonsi et al, 2022;Conte et al, 2022;Gorgoni, Scarpelli, Alfonsi, Annarumma, et al, 2022;Meaklim et al, 2023;Scarpelli et al, 2021Scarpelli et al, , 2022. Indeed, during the first wave of the COVID-19 pandemic, participants reported higher negative emotions and longer MRDs; during the second wave, participants reported higher positive emotions and lower presence of sensory impressions in their MRDs, as well as more realistic and shorter MRDs; while, during the third wave, participants reported lower positive emotions.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, findings in the literature of longitudinal dream studies during the different waves of COVID-19 (e.g., Alfonsi et al, 2022; Conte et al, 2022; Goncalves et al, 2022; Gorgoni, Scarpelli, Alfonsi, Annarumma, et al, 2022; Scarpelli et al, 2021, 2022) highlighted that its impact persisted on dream features, such as frequency, length, vividness, and negative emotionality, despite a sort of adaptation to the pandemic situation (e.g., Conte et al, 2022; Meaklim et al, 2023). More in particular, research findings have shown a decrease in dream frequency, length, emotional load, vividness, and bizarreness after the total first wave lockdown, as well as a reduction in specific lockdown-related dream themes, but no significant modifications in the negative dream emotional tone (e.g., Alfonsi et al, 2022; Gorgoni, Scarpelli, Alfonsi, Annarumma, et al, 2022; Scarpelli et al, 2022).…”
Section: The Current Study: Aims and Hypothesesmentioning
confidence: 99%
“…The pandemic was portrayed as a lethal enemy and health experts were portrayed as “heroes fighting on the front line in a battle ” [ 12 , 49 ]. Moreover, the challenge relating to the struggle with forces greater and stronger than the dreamer (e.g., wild nature, animals, falling) may have represented efforts to describe more profoundly the threats and terror individuals had to cope with during this period [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that OSA was associated with a hormonal imbalance, which might probably be linked with impaired reproductive functions and associated comorbidities. Another COVID-19 paper was authored by Meaklim et al (2023) and deals with the interesting topic of dreams during the pandemic.…”
mentioning
confidence: 99%
“…Another COVID‐19 paper was authored by Meaklim et al (2023) and deals with the interesting topic of dreams during the pandemic. Of >2,000 participants of a global survey examining insomnia symptoms, dreams, and mental health, which was launched in 2020 and followed participants over 12 months, 45% reported dream changes at baseline.…”
mentioning
confidence: 99%